2006
DOI: 10.1542/peds.2005-1847
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Nonchemical Treatment for Head Lice: A Lot of Hot Air

Abstract: Our findings demonstrate that one 30-minute application of hot air has the potential to eradicate head lice infestations. In summary, hot air is an effective, safe treatment and one to which lice are unlikely to evolve resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…One study showed that subjects had nearly 100% mortality of eggs and 80% mortality of hatched lice. 70 The machine is expensive, and the operator requires special training in its use. A regular blow-dryer should not be used in an attempt to accomplish this result, because investigators have shown that wind and blow-dryers can cause live lice to become airborne and, thus, potentially spread to others in the vicinity.…”
Section: Desiccationmentioning
confidence: 99%
“…One study showed that subjects had nearly 100% mortality of eggs and 80% mortality of hatched lice. 70 The machine is expensive, and the operator requires special training in its use. A regular blow-dryer should not be used in an attempt to accomplish this result, because investigators have shown that wind and blow-dryers can cause live lice to become airborne and, thus, potentially spread to others in the vicinity.…”
Section: Desiccationmentioning
confidence: 99%
“…Each year, millions of children are infested with head lice, a condition known as pediculosis, which is responsible for tens of millions of lost school days. Head lice have evolved resistance to many of the currently used pediculicides; therefore, an effective new treatment for head lice is needed (Goates et al 2006). P. humanus capitis infestation is a major concern in public health.…”
Section: Introductionmentioning
confidence: 99%
“…One study showed that subjects had nearly 100% mortality of eggs and 80% mortality of hatched lice. 61 The machine is expensive, and the operator requires special training in its use. A regular blow dryer should not be used in an attempt to accomplish this result, because investigators have shown that wind and blow dryers can cause live lice to become airborne and, thus, potentially spread to others in the vicinity.…”
Section: Desiccationmentioning
confidence: 99%